STRENGTHENING LOCAL FISCAL RESILIENCE: GOVERNANCE AND POLICY RESPONSES TO FINANCIAL DISTRESS - Anggi Mega Rizki; Rindu Rika Gamayuni; Pigo Nauli (Faculty of Economics and Business, 2026)
Fiscal resilience at the local government level has become a critical issue in public financial management, particularly in the context of rising fiscal pressures and persistent dependence on intergovernmental transfers. These conditions have direct implications for the quality of public service delivery and the stability of the national fiscal system. This study examines the role of governance and policy interventions in addressing financial distress as a pathway to achieving fiscal resilience in local governments. Departing from prior studies that predominantly emphasize financial ratios, this research underscores the significance of governance arrangements and central government interventions as strategic responses to local fiscal stress, offering a more comprehensive and systematic synthesis of the existing literature. Using a Systematic Literature Review approach based on the SPAR-4-SLR framework, this study analyzes 15 Scopus-indexed articles published between 2007 and 2025 through thematic analysis. The results indicate that local fiscal resilience is shaped not only by financial indicators but also by the quality of governance, local political structures, and the effectiveness of policy interventions in responding to fiscal pressures. These findings suggest that sustainable fiscal resilience can be achieved through the strengthening of local governance capacities and the implementation of adaptive and responsive policy interventions aligned with the dynamics of local fiscal risks.